2019
DOI: 10.1111/cpr.12710
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐clinical evidences for the efficacy of tryptanthrin as a potent suppressor of skin cancer

Abstract: Objective Clinical trials have demonstrated the efficacy of indigo naturalis, a traditional Chinese medicine ingredient, against psoriasis, a skin disease characterized by keratinocyte hyperproliferation and inflammation. The present study investigates the efficacy of tryptanthrin, a bioactive compound in indigo naturalis, against non‐melanoma skin cancer (NMSC) and the signalling events involved. Methods Efficacy of tryptanthrin against NMSC was assessed using DMBA/PMA‐induced skin carcinogenesis model in Swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Recently, tryptanthrin has also been shown to be an effective suppressor of non-melanoma skin cancer (NMSC), as demonstrated by using dimethylbenz[a]anthracene/phorbol 12myristate 13acetate (DMBA/PMA) induced skin carcinogenesis model in Swiss albino mice [79]. It was found that the compound disrupted DMBA/PMA-induced expansion of hair follicle cells by suppressing the activation of β-catenin, which is a major driver of hair follicle cell proliferation.…”
Section: Anti-tumor Activitymentioning
confidence: 99%
“…Recently, tryptanthrin has also been shown to be an effective suppressor of non-melanoma skin cancer (NMSC), as demonstrated by using dimethylbenz[a]anthracene/phorbol 12myristate 13acetate (DMBA/PMA) induced skin carcinogenesis model in Swiss albino mice [79]. It was found that the compound disrupted DMBA/PMA-induced expansion of hair follicle cells by suppressing the activation of β-catenin, which is a major driver of hair follicle cell proliferation.…”
Section: Anti-tumor Activitymentioning
confidence: 99%
“…The first search was made in order to assess the scientific interest in the topic. The second search had the following steps: Introduction of words and limits in PubMed with first step exclusion criteria for articles that did not refer to a potential substance for topical therapy, formulas from traditional medicine that did not specify the active ingredient (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The second step exclusion criterion was if the substance of interest was not administered topically.…”
Section: Methodsmentioning
confidence: 99%
“…Tryptanthrin could significantly reduce the size and multiplicity of skin tumors. In addition, tryptanthrin impeded the diffusion of hair follicle cells by interfering with the activity of β-catenin and inhibited A431 cells by abolishing the activation of β-catenin (Shankar et al, 2019). Moreover, the oxygen atom at position 6 of the tryptanthrin ring was coupled to heme iron of tryptophan 2,3-dioxygenase, which was a therapeutic target in cancer diseases, via coordination interaction and thus exhibited higher tryptophan 2,3-dioxygenase inhibitory activity (Zhang et al, 2018).…”
Section: Antitumor Effectmentioning
confidence: 99%